Case Report of an Hepatoid Adenocarcinoma of the Stomach. Issue 2 (February 2016) - Gaeta, Raffaele; Ugolini, Clara; Castagna, Maura
Abstract : Hepatoid adenocarcinoma (HAC) is a rare but important type of extrahepatic tumor that has a morphologic similarity to hepatocellular carcinoma, with production of α-fetoprotein in high amounts and a poor prognosis. Stomach is one of the organs in which HAC has been most commonly identified. We report a case of an old man with a polypoid mass in the prepyloric region. The microscopical aspects were suggestive for an undifferentiated adenocarcinoma, but the positive immunohistochemical staining for α-fetoprotein, α-1-antitrypsin, α-1-antichymotrypsin, and Hep Par1 were crucial for the final diagnosis of hepatoid adenocarcinoma of the stomach. Because of the poor prognosis for this type of tumor, correct and early-stage diagnosis of HAC is essential and long-term follow-up is required.